Heretic : a memoir - Kadlec, Jeanna (Harper, an imprint of HarperCollins Publishers, 2022)
Jeanna Kadlec knew what it meant to be faithful--in her marriage to a pastor's son, in the comfortable life ahead of her, in her God--but there was no denying the truth that lived under that conviction: she was queer and, if she wanted to survive, she would need to leave behind the church and every foundational building block she knew. Heretic is a memoir of rebirth. Within, Kadlec reckons with religious trauma and Midwestern values, as a means of unveiling how evangelicalism directly impacts every American--religious or not--and has been a major force in driving our democracy towards fascism. From the story of Lilith to celebrity purity rings, Kadlec interrogates how her indoctrination and years of piety intersects with her Midwest working-class upbringing. As she navigated graduate school, a new home on the East Coast, and a new marriage, another insidious truth began to reveal itself --that conservative Christianity has both built and undermined our political power structures, poisoned our pop culture, and infected how we interact with one another in ways that the secular population couldn't see. Weaving the personal with powerful critique, Heretic explores how we can radically abandon these painful systems by taking a sledgehammer to the comfortable.